Applying chlorogenic acid in an alginate scaffold of chondrocytes can improve the repair of damaged articular cartilage - Cheng, Xin (PLoS One, 2018)
Damaged cartilage has very low regenerative potential which has led to the search for novel tissue-engineering approaches to help treat cartilage defects. While various approaches have been reported, there is no perfect treatment currently. In this study we evaluated the effects of a plant extract, chlorogenic acid (CGA), as part of chondrocyte transplantation on a model of knee joint injury in chicks. First, primary cultured chondrocytes used to evaluate the effects of CGA on chondrogenesis. Then using an articular cartilage injury model of chick knee we assessed the functional recovery after transplantation of the complexes containing chondrocytes and CGA in an alginate scaffold. Histological analysis, PCR, and western blot were further used to understand the underlying mechanisms. We showed that 60 μM CGA in alginate exhibited notable effects on stimulating chondrogenesis in vitro. Secondly, it was shown that the application of these complexes accelerated the recovery of injury-induced dysfunction by gait analysis when followed for 21 days. Histochemical analysis demonstrated that there was less abnormal vasculature formation, more chondrocyte proliferation and cartilage matrix synthesis in the presence of the complexes containing CGA. We discovered CGA treated transplantation up-regulated the expressions of Sox9 and Col2a1 which were responsible for the stimulation of chondrogenesis. Furthermore, the application of these complexes could suppress the abnormal angiogenesis and fibrosis at the injury site. Lastly, the elevated levels of inflammatory cytokines IL-1β, TNF-α, p-p65, and MMPs expression were decreased in the presence of CGA. This may be caused through adjusting cellular redox homeostasis associated with Nrf2. This study suggests that combining chondrocytes and CGA on an alginate scaffold can improve the recovery of damaged articular cartilage.